MAZAHIR AL-WASATIYYAH FII ISLAM ‘IND YUSUF AL-QARDAWI DALAM KITAB FIQH AL-WASATIYYAH AL-ISLAMIYYAH WA AT-TAJDID - Santi Nariswari Maduratna (Universitas Kiai Abdullah Faqih Gresik, 2025)
The purpose of this study is to determine how the manifestation of Islamic moderation according to Yusuf Al-Qardawi in the book Fiqh Al-Wasatiyyah Al-Islamiyyah Wa At-Tajdid. The research method used is the library research method. The results of this study are that Islam is moderate in belief and conception, moderate in worship and asceticism, moderate in ethics and morals, and moderate in legislation and order. Islam is a middle way in belief between superstitious people who are extreme in their beliefs, believe in everything and have faith without proof, and materialists who deny everything beyond the senses and do not listen to the voice of instinct, the call of reason, or the evidence of miracles. Islam calls for belief and faith, but only based on conclusive evidence and absolute proof. Islam is a middle way in worship and rituals, between religions and sects that have eliminated the divine aspect of worship, asceticism, and deification from their philosophy and duties. Islam represents a moral middle ground between extreme idealists who imagine humans as angels or pseudo-angels and impose impossible values ??and morals on them. Islam is also moderate in its legislation, legal system, and social system. Anyone who reflects on it and compares it with other countries will find that Islam is consistently moderate.